Catheter contact angle influences local impedance drop during radiofrequency catheter ablation: Insight from a porcine experimental study with 2 different LI‐sensing catheters. (22nd January 2022) - Matsuura, Gen; Fukaya, Hidehira; Ogawa, Emiyu; Kawakami, Sota; Mori, Hitoshi; Saito, Daiki; Sato, Tetsuro; Nakamura, Hironori; Ishizue, Naruya; Oikawa, Jun; Kishihara, Jun; Niwano, Shinichi; et al.
Abstract: Background: Local impedance (LI) can indirectly measure catheter contact and tissue temperature during radiofrequency catheter ablation (RFCA). However, data on the effects of catheter contact angle on LI parameters are scarce. This study aimed to evaluate the influence of catheter contact angle on LI changes and lesion size with two different LI‐sensing catheters in a porcine experimental study. Methods: Lesions were created by the INTELLANAV MiFi™ OI (MiFi) and the INTELLANAV STABLEPOINT™ (STABLEPOINT). RFCA was performed with 30 W and a duration of 30 s. The contact force (CF) (0, 5, 10, 20, and 30 g) and catheter contact angle (30°, 45°, and 90°) were changed in each set ( n = 8 each). The LI rise, LI drop, and lesion size were evaluated. Results: The LI rise increased as CF increased. There was no angular dependence with the LI rise under all CFs in the MiFi. On the other hand, the LI rise at 90° was lower than at 30° under 5 and 10 g of CF in STABLEPOINT. The LI drop increased as CF increased. Regarding the difference in catheter contact angles, the LI drop at 90° was lower than that at 30° for both catheters. The maximum lesion widths and surface widths were smaller at 90° than at 30°, whereas there were no differences in lesion depths. Conclusion: The LI drop and lesion widths at 90° were significantly smaller than those at 30°, although the lesion depths were not different among the 3 angles for the MiFi and STABLEPOINT.